Monetary and macroprudential policy in a commodity exporting economy: A structural model analysis - Gan-Ochir Doojav; Undral Batmunkh (Central Bank Review, 2018)
We build a structural small open economy model to examine the impact of monetary and macroprudential policy actions in a commodity exporting economy. The model incorporates labor market, credit market, macroprudential policy tools such as time-varying capital and reserve requirements, and shocks of FDI, commodity demand and commodity price. The model is estimated by Bayesian techniques using quarterly data for Mongolia in 2005–2017. The main results are (i) external and government spending shocks play important role on the business cycle fluctuations, (ii) capital and reserve requirements are more effective in curbing the credit growth (or changing bank lending rate), while the policy rate has stronger impact on inflation and exchange rate compared to the macroprudential tools, and (iii) combining macroeconomic and monetary policy measures is important in reducing welfare loss. These results suggest that synergies between monetary and macroprudential policy may ensure both macroeconomic and financial stability. Keywords: Commodity shocks, Macroprudential policy, Monetary policy, Reserve requirements, Capital requirements, Small open economy model, Bayesian analysis, JEL classification: C11, C51, E52, E58